A MEMÓRIA E O TEMPO HISTÓRICO EM FACE À DITADURA MILITAR NO CONTEXTO DAS UNIVERSIDADES EM O LUGAR MAIS SOMBRIO, DE MILTON HATOUM (Muitas Vozes, 2024)
In the trilogy, The most sombre place, Hatoum innovates his narrative technique, when working with multiple spatio-temporal planes, where, above all, the voice of the character Martim extends, who, as he composes a historical-memorial archive, draws the sociopolitical scenario of one of the most troubled and oppressive periods in recent Brazilian history. In this, the present article intends, based on her elaborations, analysismeneutics of Ricoeur, as witnesses between historical and written testimony, which configure, through the bias of the narrative, an archival. We will also make use of the research by Motta (2014), on the context of universities in the military dictatorship, to interpret the artistic-cultural and intellectual actions developed by the young people with whom Martim has a relationship at two important universities, UnB and USP.